Kepemimpinan Kepala Madrasah Menyikapi Pandemi Covid-19; Studi Kebijakan Penguatan Inteligensi Siswa - Dalimunthe, Amsal Qori; Naldi, Anri; Nurriski, Fayza (Sekolah Tinggi Agam Islam Sumatera Medan, 2022)
This study aims to analyze the policy of madrasa principals in improving the quality of education during the Covid-19 pandemic. This research was conducted at Madrasah Aliyah Negeri 2 Deli Serdang. This study uses a qualitative research method with a case study approach. The main informant of the research was the head of the madrasah, and the supporting informants were teachers of the Islamic education science group of 5 people. Collecting data using observation techniques, interviews, and documentation studies. Data analysis was carried out with the stages of data reduction, data presentation and concluding. The results showed that there were several policies of the head of the madrasa, namely: (1) strengthening students' spirituality through the Koran and tahfiz Qur'an programs, (2) strengthening student intelligence through learning according to the curriculum structure and tahfiz Qur'an, (3) strengthening student morals by implementing independent learning, and honesty-based learning. All of these activities are carried out in two forms, namely online and the wave learning system. The implications of this research are of course in improving the quality of education, especially at the Madrasah Aliyah level.